2023
DOI: 10.1021/jacsau.3c00014
|View full text |Cite
|
Sign up to set email alerts
|

Conquering the Synthesis and Functionalization of Bicyclo[1.1.1]pentanes

Abstract: Bicyclo[1.1.1]pentanes (BCPs) have become established as attractive bioisosteres for para-substituted benzene rings in drug design. Conferring various beneficial properties compared with their aromatic "parents," BCPs featuring a wide array of bridgehead substituents can now be accessed by an equivalent variety of methods. In this perspective, we discuss the evolution of this field and focus on the most enabling and general methods for BCPs synthesis, considering both scope and limitation. Recent breakthroughs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…Merging two independent p-systems to a new, cyclic core motif gives an opportunity to rapidly build up molecular complexity and access unprecedented chemical space, lately acclaimed in pharmaceuticals, agrochemical, and materials industries. [47][48][49][50] In this vein, unique cycloaddition reactions proceeding via energy transfer (for triplet energies, see Fig. 6), importantly, including dearomatization reactions, have been developed in recent years showing the potential of this constructive strategy to build 3D frameworks.…”
Section: Cycloadditionsmentioning
confidence: 99%
“…Merging two independent p-systems to a new, cyclic core motif gives an opportunity to rapidly build up molecular complexity and access unprecedented chemical space, lately acclaimed in pharmaceuticals, agrochemical, and materials industries. [47][48][49][50] In this vein, unique cycloaddition reactions proceeding via energy transfer (for triplet energies, see Fig. 6), importantly, including dearomatization reactions, have been developed in recent years showing the potential of this constructive strategy to build 3D frameworks.…”
Section: Cycloadditionsmentioning
confidence: 99%
“…In the context of γ-secretase modulation, scientists at Roche showed that noncanonical isosteric replacement of azabicyclo[3.2.1]­octane ( 1.6 ) could retain activity and increase logD (Figure C, 1.7 ) . Ma, Qin, Baran, and MacMillan independently conquered the syntheses of bridge-substituted BCPs, which could add additional exit vectors to mimic polysubstituted arenes . 1,2-Disubstituted BCPs replace ortho -disubstituted arenes and can increase solubility (e.g., boscalid 1.4 vs 1.5 , >20-fold increase in kinetic solubility, or telmirsartan in ref ) and reduce clearance.…”
Section: [111]propellane and Higher Propellanesmentioning
confidence: 99%
“…The latter, however, may in turn facilitate the rapid advance of the former. As a paradigm, the synthesis of bicyclo[2.1.1]­hexanes (BCHs) has attracted increasing attention from chemists in recent years due to the ability of these rigid hydrocarbons to serve as ideal bioisosteres of ortho or meta-substituted benzenoids (Scheme A) to improve the metabolic stability of corresponding drug analogues. As a result, a wide range of efficient intermolecular [2π + 2σ] cycloaddition reactions of bicyclo[1.1.0]­butanes (BCBs) with olefins have been developed, originating from the widespread availability of both feedstock and the ability to conveniently assemble diverse substituents on BCHs. Among them, the Procter and Wang groups have established the SmI 2 and pyridine-diboron-engaged catalytic systems, respectively, to trigger the transformations by single electron transfer (SET). , Furthermore, photocatalysis as a green and sustainable platform for radical chemistry has been leveraged by Glorius and Brown to accomplish energy transfer (EnT)-enabled cycloadditions of BCBs with various cyclic and acyclic olefins (Scheme B). , In this regard, photoredox catalysis as another powerful tool for the production of radical species has never been applied to such an important chemical transformation, and its viability may provide an opportunity to make feasible those incompatible substrates, such as simple BCBs containing phenyl ketones, in the energy transfer platform . As another noteworthy issue, a large number of BCHs contain stereocenter(s) (Scheme A), revealing that replacing benzenoids by either R - or S -enantiomers of BCHs may lead to distinct bioactivities of the drug.…”
Section: Introductionmentioning
confidence: 99%